Expression of Stimuli in Buryat Emotion Causation Constructions - Elena K. Skribnik (Монголоведение)
Goals. This paper discusses strategies of expressing Stimuli in Buryat emotive causative constructions. Results. We argue that a series of such constructions can be seen as a system that allows the speaker to put different components of the Stimulus event into the focus of attention, depending on their informational relevance to the speaker. The component in focus of attention is represented as a main clause subject; it can be the Stimulus event as a whole (expressed by a subject clause or an action noun) or its first argument (an Agent, understood as a Causer); with a Causer as a subject, the central inanimate argument can be additionally expressed as an Instrument or the action itself as a Means (in both cases the instrumental case is used). The focus of attention on further arguments is not registered. As the study has shown, relevant for the analysis is the structure of a potential full clause describing the Stimulus and characteristics of its components: an animate or inanimate noun as a subject, a verbal or nominal predicate, a transitive or intransitive verb. Materials. The research is based on the language data from dictionaries and Buryat literary texts, including those published in the Buryat National Corpus, as well as on elicitation data. In the analysis we used descriptive, comparative and transformational methods, introspection and elicitation.